Avaliação da condição periodontal em indivíduos residentes em uma área rural do sul do Brasil - Ferreira, Ciandra Miraglia (2022)
Estimation on epidemiological level the prevalence of individuals with health individuals, as well as conditions that need treatment are essential for both planning and treatment in dental care in private and public services. The aim of this study was to evaluate the prevalence of invidivuals healthaccording to epidemiological definition of health gingival, as well as to estimate periodontal treatment need according periodontal inflammation clinical status classified as unstable post periodontal treatment. The analyzed data are secondary from epidemiological survey in a rural area of Rosário do Sul. For this study, 527 individuals with 10 or more teeth were analysed. Two examiners trained and calibrated performed complete periodontal clinical examinations at 6 sites per tooth. Behavioral, demographic and socioeconomic data were obtained through questionnaire. Periodontal health was estimated according to the recently proposed epidemiological health criterion. Periodontal condition associated with unstable cases were estimated. Logistic regression using an architectural model was built to estimationg associate variables with unstable cases. A low prevalence of epidemiological health was observed. A high porcentage of individuals were classified as unstable and were associate with dental plaque and gingival inflammation. Can be conclude that a high demand for periodontal treatment is necessary for re-established gingival/periodontal health in this sample.